Relasi Hak dan Kewajiban Lingkungan dalam Kehidupan Bertetangga - Hadi Mustopa; Metty Sander; Putri Jecika Fujianti; Taufiq Supriadi (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Environmental protection and management in the context of residential communities cannot be separated from the relationship between the rights and obligations of citizens. The right to a good and healthy environment, as guaranteed in the 1945 Constitution of the Republic of Indonesia and Law Number 32 of 2009 concerning Environmental Protection and Management, must go hand in hand with the obligation of society to maintain and preserve the environment. This article aims to analyze the relationship between environmental rights and obligations in neighborhood life through an empirical study in RT 08 RW 04 Malaka Jaya, East Jakarta. This study employs an empirical legal research method with a socio-juridical approach. The results show that the balance between environmental rights and obligations is a key factor in creating social and ecological harmony at the community level. Environmental practices developed in RT 08 demonstrate that environmental law functions not only as an instrument of enforcement but also as a means of fostering collective awareness and preventing environmental conflicts at an early stage.